Pajak Bumi Bangunan Sebagai Bagian Dari Penerimaan Daerah (Berdasarkan Undang-Undang Nomor 28 Tahun 2009 tentang Pajak Daerah dan Retribusi Daerah) - Oktavina, Helen (Jurnal Ilmiah Wahana Pendidikan, 2024)
Law of the Republic of Indonesia Number 28 of 2009 concerning Regional Taxes and Regional Levies Which makes Rural and Urban Land and Building Taxes the responsibility of regiona governments. Tax is a source of state revenur that contributes greatly in financing the needs of state spending an national development. Seeing that taxes are one of the main sources of revenue today, the government is trying to increase revenue receipts from this sector. The research method this time uses a normative legal research method based on Law No. 28 of 2009. The scope of this research discussion is about what efforts can optimize regional revenues from Land and Building Tax sources. Law Number 28 0f 2009 concerning Regional Taxes and Regional Levies as the legal basis for regional revenues and how they are implemented. In conclusion, optimizing regional income through taxes can be done in 3 ways, namely extensification, intensification and institutional strengthening, Law no. 28 of 2009 as a legal basis there was an overlap in its implementation which resulted in high economic costs in terms of tax collection, its current implementation often clashes with the interests of the central government in the area in terms of tax collection which resulst in excessive absorption of the community in which the regions take levies. As a source of income other than optimizing income from land and building taxes.